Pengaruh Kompetensi, Motivasi dan Budaya Organisasi terhadap Kinerja Pegawai yang Dimoderasi Oleh Gaya Kepemimpinan - Buchori, Buchori; Kirlan, Sanjoyo; Waskito , Meindro (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Employee performance is a critical factor in achieving organizational goals, especially in strategic institutions such as the National Counterterrorism Agency (BNPT), which is tasked with maintaining national stability and security. Although the number of civil servants (ASN) at BNPT has increased over the past five years, data shows that the Employee Performance Target (SKP) scores have tended to decline during the 2021-2023 period, indicating the need to identify factors influencing employee performance. This study aims to analyze the direct and indirect effects of competence, motivation, and organizational culture on employee performance, with leadership style as a moderating variable. This study uses a quantitative approach with descriptive and explanatory survey methods conducted at the BNPT, involving 150 employees selected using proportional random sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4 software. The results indicate that competence (p-value = 0.607) and motivation (p-value = 0.413) do not directly influence employee performance, while organizational culture has a positive and significant influence on employee performance (p-value = 0.001; t-statistic = 3.345). Leadership style does not moderate the relationship between competence and performance, but significantly moderates the relationship between motivation and employee performance with a p-value of 0.013 and a t-statistic of 2.486. There is no moderating effect of leadership style on the relationship between organizational culture and employee performance. This study contributes to the development of human resource management literature in the strategic public sector and provides practical recommendations for improving employee performance through strengthening organizational culture and optimizing appropriate leadership styles.